Site-Specific Dissemination of CIS-CSA Innovation to AICCRA-Ghana Beneficiaries and Adoption Evidence - Kyeremeh, Emmanuel Marfo; Koi, Gordon Nii (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The paper evaluated the site-specific dissemination of Climate Information Services and Climate-Smart Agriculture (CIS-CSA) innovations to AICCRA-Ghana beneficiaries by Esoko. It seeks to assess achievements, challenges, and adaptation evidence resulting from this initiative. Esoko delivered over 87,800,000 CIS-CSA messages to 350,860 project targets in 2023. Adoption evidence shows that CIS-CSA advisories have positively impacted adaptive capacities and empowered them to make informed decisions in response to changing weather patterns.